MAKNA KATA ITHMA’ANNA DAN DERIVASINYA DALAM AL-QUR’AN: (STUDI TERHADAP FORMULASI DAN SOLUSI TERAPI DEPRESI) - Raihana, Lidya (Khulasah : Islamic Studies Journal, 2025)
This thesis explores solutions and formulations for depression therapy by examining the derivation of the word ’Ithma’anna’ in the Al-Qur’an, which means ’calm’. Currently, there are so many cases regarding mental health, especially depression. Depression is a feeling of excessive sadness, frustration, feeling worthless, feeling unable to solve problems, and often even ending in suicide. So the main thing that people who experience depression need most is peace of mind and soul. In the Qur’an, the word calm which has a connotation of mental health, is Ithma’anna. So, researchers will examine the meaning of Ithma’anna in the Al-Qur’an as a solution and formulation for depression therapy. This research is library research with a thematic interpretation approach. References for this study are taken from several primary and secondary sources. This research took several steps in data collection. After that, the data obtained was analyzed using descriptive and linguistic analysis methods. The results of this research, based on a study of several letters containing the word Ithma’anna, can be obtained through dhikrullah (remembering Allah), being pleased with the strictness that Allah has given, having strong faith, and believing in the good news that Allah has promised for people. people who are willing to be patient in navigating all the problems and tests of life in this world.